(untitled) (International Journal of Mosque, Zakat And Waqaf Management (Al-Mimbar), 2023)
Mosques are known as an institution that, in addition to being places of worship, administrative centers, economic powerhouses, and social centers, promotes community education. Due to alterations in information distribution and the community’s increased reliance on digital media, the COVID-19 epidemic has significantly impacted the effectiveness of Islamic da’wah. Although the potential of mosques as informal study centers has been investigated, there is a gap in research that systematically gathers and emphasizes literature on the use of digital media for the informal sharing of information in response to economic shifts. Therefore, this study mainly investigates the role of mosques as centers for informal knowledge exchange assisted by digital technology. This is a contemporary kind of da’wah that has the direct capacity to exert influence and shape society. This study used the PRISMA methodology, an acronym for Preferred Reporting Items for Systematic Review and Meta-Analysis. The main data sources used for finding relevant sources in this systematic literature review (SLR) were Scopus, Web of Science, and Science Direct. The study has discovered four main themes: the potential of mosques, the spread of knowledge, the use of new media, and informal learning. The study’s results are anticipated to aid policymakers, practitioners, and academics in developing ideal modules as a benchmark for contemporary da’wah practices. Therefore, this study is expected to be used as a reference point for future studies investigating how digital technology might improve the informal transfer of knowledge in mosques.